Novel biocides for cultural heritage - Silva, Mara Teresa Caldeira da (2017)
Many microorganisms, influenced by environmental conditions, are the main responsible for biological contamination in built heritage. Biocides based on chemical toxic compounds have been the most often used to mitigate this problem. Thus, it is of vital importance to develop proper remediation actions based on environmentally innocuous alternatives. Bacteria of the genera Bacillus are emerging as an optimistic alternative due to their capacity to produce secondary metabolites with antagonistic activities against many fungal pathogens. This work aimed to develop ground-breaking research in the area of cultural and built heritage rehabilitation, by the development of natural and green safe biocides for biodegradation/biodeterioration treatment of Cultural Heritage. A complementary methodology, including antifungal tests and molecular approaches was used, in combination with microscopic and analytical techniques to detect, characterise and study the efficiency of the biological active compounds produced by Bacillus sp. strains. Flow cytometry allowed a comprehensive study of the physiological mechanism behind the bioactive compounds production in order to understand and improve the strategic approaches for process optimisation and scale up production. Moreover, according to the results of the toxicological tests, these compounds have proven to be a real environmental safe and innocuous alternative to the chemical biocides commonly used during the conservative interventions. Thus, they have shown a great potential for their future application in cultural and built heritage rehabilitation; Novos Biocidas para o Património Cultural Resumo: Vários microrganismos influenciados pelas condições ambientais são os principais responsáveis pela contaminação biológica do património cultural edificado. Na tentativa de mitigação destes agentes, compostos geralmente tóxicos têm sido os mais utilizados. Assim, é de enorme importância desenvolver ações de remediação dirigidas aos agentes efetivamente biodeteriogénicos, baseados em alternativas inócuas para o meio ambiente. As bactérias do género Bacillus surgem, como uma viável alternativa devido à capacidade de produzir metabolitos secundários com atividade antagonista, contra diversos fungos. Este trabalho teve como objetivo desenvolver uma investigação inovadora que possa vir a ser útil na área de reabilitação do património cultural edificado, através da produção de novos biocidas naturais e mais ecológicos. Utilizou-se uma abordagem metodológica, que incluiu testes antifúngicos e abordagens moleculares, combinadas com técnicas microscópicas e analíticas, de forma a detetar, caracterizar e estudar a eficiência de compostos biologicamente ativos produzidos por estripes de Bacillus sp.. Foram ainda utilizados os mecanismos fisiológicos por detrás da produção destes compostos, de forma a perceber e melhorar as abordagens estratégicas no processo de otimização da produção. Em testes toxicológicos, compostos produzidos por estirpes de Bacillus sp. selecionados, provaram ser uma alternativa ecológica aos biocidas químicos, comumente utilizados em intervenções de conservação. Desta forma, estes demonstram um elevado potencial para futura utilização na reabilitação do património cultural edificado.